Image et classe de langue: quels chemins didactiques? - Demougin, Françoise (Linguarum Arena, 2018)
This article focuses on the use of the image in a language class. Starting again from previous studies, the author intends to analyze first the characteristics of the image as support for course, then the uses of the image in foreign language classroom, from the example of French Foreign Language, and finally the different postures adopted by students during the reading frame. From these data, the paper examines how the teacher can accompany the reading of the image according both to the nature of the image and to the language classroom. The «log book» allows the learner to combine vision and words, to start a dialogism between self and self, self and other. The learner is thereby «involved» in an understanding of the image in action, in a process of a real ownership of the language.